ТАВДИНСКИЙ ГОРИЗОНТ И ПОЛОЖЕНИЕ ГРАНИЦЫ ЭОЦЕНА - ОЛИГОЦЕНА В ЗАПАДНОЙ СИБИРИ - Подобина Вера Михайловна (My University, 1988)
The data on the distribution of the foraminifers and ostracods in Tavda Suite in eastern part of Western Siberia are considered. At the base of Tavda Suite the Elphidiel- la vergandia Zone is recognized. This zone belongs to the Lower Oligocene and the Eoce- ne-Oligocene boundary to be placed at the bottom of the Tavda Horizon.
Keywords: Олигоцен; Эоцен; Кайнозой::Палеоген::Олигоцен; Кайнозой::Палеоген::Эоцен